Estresse e coping em trabalhadores de enfermagem de um hospital privado - Benetti, Eliane Raquel Rieth (2013)
This study aimed to analyze stress and Coping in nursing workers at a private hospital. This is a cross sectional, analytical and quantitative study, performed with 209 nursing workers of a private hospital in Rio Grande do Sul northwest. Data were collected between September and October 2012, after Free and Informed Consent Term (FICT) signature, through a research protocol that included: Form to sociodemographic and functional characterization, Work Stress Scale (WWS) and Coping Strategies Inventory (CSI). This investigation included determinations recommended by Resolution 196/96 of the National Health Council(NHC) and was approved by Ethics Committee of the Santa Maria Federal University/ RS (CAAE: 06163312.8.0000.5346). For storage and organization of information, we built a database in an electronic spreadsheet in Excel (Office 2007). Sociodemographic and functional variables and items of instruments were statistically analyzed with the Statistical Package for the Social Sciences (SPSS - version 17.0). Satisfactory internal consistency was attested for the ETT (Alpha= 0.914) and the IEC (Alpha= 0.897). There was a predominance of females, married, with one or more children, of aged between 30 and 39 years, who lives at Ijuí city and take less than 30 minutes to arrive at hospital. About functional characteristics, we found that 83.25% are nursing technicians, 41.15% completed the training (higher/professionalizing) within the last five years, 29.67% work in the institution between two and four years and 30 , 14% work in the unit that are crowded for the same period. Still, 55.02% chose unit that would like to work, 51.20% were trained to perform their job in unit they are scaled and 53.11% have academic or other labor activity. We observed that 52.15% perform physical activities and 67.94% enjoy of leisure moments. In this study, 71.29% of nursing workers showed moderate stress. WSS situations of lowest and highest mean, respectively, were: "I have felt bothered by working in tasks below my skill level" and "I'm angry at discrimination / favoritism in my work environment". Coping Factors mostly used by nursing workers were Positive Reappraisal, Social Support and Problems Resolution. In Positive Reappraisal Factor, "prayed" was the action most used. There was a statistically significant difference between stress and training, and those who received training had lower stress means. There were significant statistically differences between sex and Self-control; Social Support and salary range; Acceptance of Responsibility and age, number of children, training and salary.